Crystallization‐Induced Enhanced Electrochemiluminescence from a New Tris(bipyridine)ruthenium(II) Derivative - Han, Tingting; Cao, Yue; Wang, Jia; Jiao, Jianmin; Song, You; Wang, Leyong; Ma, Cheng; Chen, Hong‐Yuan; Zhu, Jun‐Jie (Advanced functional materials, 2023)
Classic tris(bipyridine)ruthenium(II) complex (Ru‐bpy) with high electrochemiluminescence (ECL) efficiency still suffers from a serious aggregation‐caused quenching (ACQ) problem, which greatly weakens its ECL efficiency to restrict further applications in solid‐state ECL imaging and light‐emitting devices. Herein, the crystallization‐induced enhanced ECL (CIE‐ECL) of tris(bipyridine)ruthenium(II) derivatives (Ru‐TPE) are reported by decorating Ru‐bpy with inherent aggregation‐induced emission active tetraphenylethene (TPE), which effectively eliminates the detrimental π–π stacking interactions and thus helps Ru‐bpy surmount notorious ACQ effect in the aqueous phase. The Ru‐TPE shows negligible ECL emission in solution but produces a strong ECL emission upon crystallization. Surprisingly, the ECL efficiency of Ru‐TPE crystals is 20 and 3 times higher than that of its solution and Ru‐bpy crystals, respectively. Experimental and structural analysis reveals that such a CIE‐ECL effect originates from the restricted intramolecular rotation and ordered molecular packing. Moreover, the high‐resolution ECL imaging of a single Ru‐TPE crystal is successfully demonstrated. This work provides a new design strategy for achieving high efficiency in solid‐state ECL imaging and devices. A new tris(bipyridine)ruthenium(II) derivative (Ru‐TPE) is synthesized and realizes the crystallization‐induced enhanced electrochemiluminescence (CIE‐ECL), which originates from the restricted intramolecular rotation and ordered molecular packing. Besides, the high‐resolution ECL imaging of a single Ru‐TPE crystal is successfully demonstrated.